Comportamento mecânico de um solo reforçado com fibra de Curauá (Ananas erectifolius) - Silva, Erico Rafael da (2020)
The application of reinforcement with fibers in soils has been introduced with the purpose to provide this material with improvement in its reforms in soils arose with the use of mechanical properties, especially in shear stress. Curaua (Ananas erectifolius) fibers, when compared to other vegetable fibers have high mechanical resistance, many times, to overcome the deficiencies of the material to be reinforced. The objective of this study was to evaluate the addition of vegetable fiber in the mechanical behavior of a silty soil in the city of Curitiba, in the state of Paraná in Brazil. The influence of variations in fiber content and length added to the soil were evaluated. The studied lengths were 6, 15 and 30 mm and the contents were 0.25, 0.50 and 0.75% in relation to the dry mass of soil. Initially, the physical indexes of the natural soil (specific weight, moisture content) and the physical properties of the vegetable fiber (density, pH) were defined. Later, the fibers are randomly placed on the soil to make cylindrical specimens of 100 mm in height and 50 mm in diameter that were used in the performance of uniaxial compression tests and split tensile strength tests. The process of mixing the fiber to the soil occurred in the same way for the production of the 10 x 10 x 2 cm specimens submitted to direct shear tests. In addition, with a view to improving the durability of vegetable fiber, the application of a waterproofing technique using expanded polystyrene (EPS) residues was studied. The reinforced soil showed better resistance in all tests results. The increase in strength was approximately 90% measured in tests of uniaxial compression and split tensile strength. These tests revealed the optimum content and length of 0.50% and 6 mm, respectively. In direct shear tests, the increase in strength at low confining stresses is proportional to the increase in fiber content and length. The application of the treatment to vegetable fiber, reduced the effects of biodegradation and influenced the reduction in 10% of water absorption increased the tensile strength of the fiber by 5%. In addition to better mechanical strength, it was also observed that the inclusion of fibers provided the soil with increased ductility and made it possible to achieve greater deformations without a sudden drop in of resistance.